Enhancing Nurses' Empathy Towards Young Child Patients Through Empathy Training - Novita Dewi; Frieda Mangunsong (Eduvest - Journal of Universal Studies, 2024)
In nursing services for early childhood hospitalized patients, nurses' empathetic attitudes cannot be implemented optimally. Empathy is a knowledge and skill that can be improved through education and training programs. Although there are many empathy training programs in nursing, there is no training programs specifically designed to increase nurses' empathy towards early childhood patients. This thesis is a research on an intervention program in the form of the "I Love and Understand You" training program which aims to increase nurses' empathy towards young children who are being treated in hospital. This research is a quantitative research with a one group difference test design before and after intervention or one group pretest post-test design. There were 18 participants in this study. Based on the Wilcoxon Signed Rank Test, the research results showed a significant increase in nurses' empathy towards early childhood before and after the intervention program was implemented (p-value < 0.001, p < 0.05). Based on the Friedman test, the research results also showed that nurses' empathy for early childhood remained significantly different two weeks after the intervention program was implemented (p-value 0.001, p < 0.05). This proves that the "I Love and Understand You" training program increases nurses' empathy for young children who are being treated in hospital.